2009
DOI: 10.1039/b910497f
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between co-adsorbed CO and H on a Rh(100) single crystal surface

Abstract: Co-adsorption of CO and H(2) on a Rh(100) single crystal surface has been studied by a combination of temperature programmed desorption (TPD), reflection absorption infrared spectroscopy (RAIRS), low energy electron diffraction (LEED), and density functional theory (DFT) calculations. Exposure of CO to a hydrogen precovered surfaces at 150 K results in some displacement of adsorbed hydrogen and a layer with 0.67 ML H and 0.67 ML CO is obtained. A c(3 square root(2) x square root(2))R45 degree structure is form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 45 publications
6
36
2
Order By: Relevance
“…Wei and Iglesia's study found an activation energy of 109 kJ/mol [18] for an assumed clean surface, which is not too far from what we found in this study. Maestri et al included coverage effects in determining the activation energy and estimated an activation energy of 62 kJ/mol at h CO = 0.15 and h H = 0.2, which corresponds well with our observed values that also include a partly coverage of CO and H. [29] and Rh(100) [30]. CO is preadsorbed at temperatures below -143°C for both sets of experiments.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Wei and Iglesia's study found an activation energy of 109 kJ/mol [18] for an assumed clean surface, which is not too far from what we found in this study. Maestri et al included coverage effects in determining the activation energy and estimated an activation energy of 62 kJ/mol at h CO = 0.15 and h H = 0.2, which corresponds well with our observed values that also include a partly coverage of CO and H. [29] and Rh(100) [30]. CO is preadsorbed at temperatures below -143°C for both sets of experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Studies of coadsorption of CO and hydrogen on Rh(100) show that hydrogen is destabilised and that some of the hydrogen desorbs at a lower temperature [30]. When there are a low number of free sites, the surface will predominantly be covered by CO. Our model predicts that the coverages for the two species, CO and H, are similar at steam reforming conditions as shown on Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4). CO-induced penetration of H atoms into subsurface interstitial sites has been reported on Pd(111) [77] and Rh(100) [78]. Kobayashi et al [80] recently reported hydrogen absorption by 1.5 ± 0.5 nm-sized iridium nanoparticles up to 0.18 H per Pt atom at 303 K and atmospheric pressure of H 2 .…”
Section: Further On the Low-temperature β 1 -H Defect Statementioning
confidence: 98%
“…3b (rescaled CO IRAS spectra). 8,26,[76][77][78] The CO also adsorbed on top of the Rh atoms, as no absorption feature for CO on bridge or hollow sites, expected in the regime 1770-1900 cm À1 , 26,76-78 was observed. The much greater absorption intensity from CO Au does not correspond to much more numerous Au sites on the bimetallic clusters, but to the greater dipole moment for CO Au on the more electronegative Au, as indicated in the DFT calculation below.…”
Section: 68mentioning
confidence: 99%